Survival, cardiovascular morbidity, and reinterventions after elective endovascular aortic aneurysm repair in patients with and without diabetes: A nationwide propensity-adjusted analysis. (December 2019) - Taimour, Soumia; Avdic, Tarik; Franzén, Stefan; Zarrouk, Moncef; Acosta, Stefan; Nilsson, Peter; Miftaraj, Mervete; Eliasson, Björn; Svensson, Ann-Marie; Gottsäter, Anders
Epidemiological data indicate decreased risk for development and growth of abdominal aortic aneurysm (AAA) among patients with diabetes mellitus (DM). On the other hand, DM adds to increased cardiovascular (CV) morbidity and mortality. In a nationwide observational cohort study of patients registered in the Swedish Vascular Register and the Swedish National Diabetes Register, we evaluated potential effects of DM on total mortality, CV morbidity, and the need for reintervention after elective endovascular aneurysm repair (EVAR) for AAA. We compared 748 patients with and 2630 without DM with propensity score-adjusted analysis, during a median 4.22 years of follow-up for patients with DM, and 4.05 years for those without. In adjusted analysis, diabetic patients showed higher rates of acute myocardial infarction (AMI) during follow-up (relative risk (RR) 1.44, 95% CI 1.06–1.95; p = 0.02), but lower need for reintervention (RR 0.12, CI 0.02–0.91; p = 0.04). There were no differences in total (RR 0.88, CI 0.74–1.05; p = 0.15) or CV (RR 1.58, CI 0.87–2.86; p = 0.13) mortality, or stroke (RR 0.95, CI 0.68–1.32; p = 0.75) during follow-up. In conclusion, patients with DM had higher rates of AMI and lower need for reintervention after elective EVAR than those without DM, whereas neither total nor CV mortality differed between groups. The putative protective effects of DM towards further AAA enlargement and late sac rupture may help explain the lower need for reintervention and absence of excess mortality.